2020
DOI: 10.1111/cea.13578
|View full text |Cite
|
Sign up to set email alerts
|

Impact of food challenge on local oesophageal immunophenotype in eosinophilic oesophagitis

Abstract: Background Eosinophilic oesophagitis (EoE) is caused by the ingestion of food antigens. Dietary avoidance can result in clinical and histological remission, while food reintroduction can cause recurrence. It is uncertain if food antigen processing and immune activation occurs locally, in the oesophagus. Therefore, we performed a comparative study of the density of cell surface proteins (known to be involved with antigen presentation) on oesophageal tissue prior to, and following food antigen induced disease re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The occurrence of oesophageal eosinophilia and inflammation in EoE is dependent at least in part on the penetration of food antigens into the oesophageal mucosa. Indeed, the presence of food antigen in the mucosa is enough to generate a Th2 allergic pathway or specific recognition of this antigen in a given patient through several potential pathways 3‐5 . In this study, we demonstrate that the oesophageal mucosa is selectively permeable to food antigens ranging from penetration based on the activity of EoE to generalised antigen entry found with inactive disease and in normal controls.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The occurrence of oesophageal eosinophilia and inflammation in EoE is dependent at least in part on the penetration of food antigens into the oesophageal mucosa. Indeed, the presence of food antigen in the mucosa is enough to generate a Th2 allergic pathway or specific recognition of this antigen in a given patient through several potential pathways 3‐5 . In this study, we demonstrate that the oesophageal mucosa is selectively permeable to food antigens ranging from penetration based on the activity of EoE to generalised antigen entry found with inactive disease and in normal controls.…”
Section: Discussionmentioning
confidence: 60%
“…This includes the role of oesophageal epithelial cells as potential nonprofessional antigen presenting cells 3 and recognition and activation of T lymphocytes by eosinophils after antigen exposure 4 . Another study has demonstrated elevation of key cell surface proteins associated with antigen presentation, such as HLA‐DR, CD3, CD28, CD40 and CD138, significantly increased with food reintroduction 5 …”
Section: Introductionmentioning
confidence: 99%
“…The esophageal epithelial barrier during active EoE is impaired and selectively permeable to food allergens that can remain in the esophageal epithelium for up to 4 days. 58 The presence and subsequent recognition of food allergens in the esophageal mucosa generates a local type 2 immune response, 59 , 60 , 61 forming a pathogenic cycle to further exacerbate allergic inflammation. Butyrate and propionate may break this cycle by restoring barrier function and thus preventing the penetration of food allergens into the esophageal mucosa and subsequent inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a good accumulated knowledge of the dominant allergens, including their cross‐reactivity patterns, 6 there is much less known about immune responses in people with food allergy and how these change over time. We know that there are specific changes in the gastrointestinal mucosa in relation to food exposure, 7 but how does the food‐allergic host respond systemically? What are the immunological associations of being food allergic?…”
Section: Figurementioning
confidence: 99%